Determine of fatigue index by using repeated anaerobic effort among some team games players from Faculty of physical Education students, Sana'a university - haidar mohamed; methar abdelghani; djaim nadjib (sports creativity, 2025)
Abstract: The current study aimed to identify the fatigue index (using repeated anaerobic effort) among some team sports players (handball, basketball, volleyball) from the students of the Faculty of Physical Education, Sana'a University, as well as to identify the significance of the statistical differences in the fatigue index among team sports players. The descriptive method was used because it is suitable for the nature of the study. The study sample consisted of (12) players who were selected purposively, and they were divided into three groups with (4) players for each game. The selected sample trains regularly and participates in competitions. The study procedures included a pilot study on three players: one handball player, one basketball player, and one volleyball player. To evaluate the anaerobic endurance test (Rast) and the fatigue index (FI), the sample completed running protocols. The anaerobic endurance test was administered after a 10-second warm-up on a track. The test consisted of six sprints covering a distance of 35 meters, with a 10-second rest period for recovery between sprints. After completing the test, the results were calculated using the following equation: Anaerobic power (watts) = weight x distance² / time³. The study results showed an increase in sprint time from the first to the sixth sprint due to a decrease in anaerobic endurance and an increase in the fatigue index resulting from the short recovery period of ten seconds. Although there were significant differences in the fatigue index among the three groups, they were not high due to the severe deficiency of adenosine triphosphate (ATP), which is necessary for sustained exercise. Running at the same efficiency and speed. Researchers recommend paying attention to anaerobic endurance (lactate tolerance) in athletes to delay the onset of fatigue.